E-Safe Sdn. Bhd. / Erzura Najwa Othman ... [et al.] - Othman, Erzura Najwa; Abdul Rashid, Shareeda; Zulkipli, Nor Wahidah; Suhaimi, Mohd Fairuz; Mohd Hamdan, Siti Khadijah (Faculty of Hotel and Tourism Management, 2004)
Name of company : E-SAFE SDN BHD. Nature of business : Manufacturer and supplier of fire fighting equipment.